Prevalence and perceived health effect of alcohol use among male undergraduate students in Owerri, South-East Nigeria: a descriptive cross-sectional study - Mayowa Morakinyo O; Chikere Ebirim IC (BMC, 2011)
Abstract Background Alcohol use during adolescence and young adulthood remains a prominent public health problem. Despite growing problems of global alcohol abuse, accurate information on the prevalence and pattern of use in Nigeria remain sparse. This study examines the prevalence and perceived health effects of alcohol use among undergraduate students in Owerri, Nigeria. Method The prevalence and perceived health effects of alcohol was estimated for 482 male undergraduates of four higher institutions in Owerri, South-East Nigeria between October 2008 and March 2009. Information was obtained using a semi-structured, self-administered questionnaire. Result The mean age of the students was 24.7 years. Majority of the respondents confirmed they were current users of alcohol given a prevalence of 78.4%, with twenty-seven percent of them being heavy drinkers (≥4 drinks per day). Reasons given by respondents for alcohol drinking include: makes them feel high (24.4%); makes them belong to the group of "most happening guys" on campus (6.6%); makes them feel relaxed (52.6%) while (16.4%) drinks it because their best friends do. Perceived health impacts of alcohol use among current users include: it enhances pleasure during moment of sex (51.1%), causes drowsiness and weakness (63.8%), may precipitate defective memory and impaired perception (64.3%) and serves as risk factor for most chronic diseases (68.5%). Conclusion High prevalence of alcohol use was established among study groups. Evaluation of full-scale community-level intervention, including community mobilisation and media advocacy aimed at supporting changes in policies on drinking, access and sales of alcohol to young people, could be helpful in reducing the trend.